Introducing the Journal Editors Discussion Interface - Julia Bottesini; Priya Silverstein; Sebastian Karcher; Colin Elman (IASSIST Quarterly, 2025)
Journal editors play an important role in advancing open science in their respective fields. However, their role is temporary and (usually) part time, and therefore many do not have enough time to dedicate towards changing policies, practices, and procedures at their journals. The Journal Editors Discussion Interface (JEDI, https://dpjedi.org) is an online community for journal editors in the social sciences that was launched in 2021, consisting of a listserv and resource page. JEDI aims to increase uptake of open science at social science journals by providing journal editors with a space to learn and discuss. In this paper, we explore JEDI’s progress in its first two years, presenting data on membership, posts, and from a members survey. We see a reasonable mix of people participating in listserv conversations and there are no detectable differences among groups in the number of replies received by thread-starters. The community survey suggests JEDI members find conversations and resources on JEDI generally informative and useful, and see JEDI primarily as a community to get honest opinions from others on editorial practices. However, JEDI membership is not as heterogeneous as would be ideal for the purpose of the group, especially when considering geographic diversity.